2001
DOI: 10.1089/104303401750148784
|View full text |Cite
|
Sign up to set email alerts
|

A New Immunodeficient Mouse Model for Human Myoblast Transplantation

Abstract: Design of efficient transplantation strategies for myoblast-based gene therapies in humans requires animal models in which xenografts are tolerated for long periods of time. In addition, such recipients should be able to withstand pretransplantation manipulations for enhancement of graft growth. Here we report that a newly developed immunodeficient mouse carrying two known mutations (the recombinase activating gene 2, RAG2, and the common cytokine receptor gamma, gammac) is a candidate fulfilling these require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…[55][56][57][58] In the present study, human FSHD myoblasts were injected into immunodeficient Rag mice, a validated mouse model for the analysis of muscle regeneration in the context of xenogenic MT. The implantation results we obtained were close to that reported previously [47][48][49] and confirmed that myoblasts prepared from unaffected FSHD muscles, even used at the 6th and 7th passages, take part into in vivo muscle regeneration. The overall number of dystrophin-positive fibers was inferior to that reported previously in immunocompetent models of muscular dystrophies in the context of syngenic or allogenic MT.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…[55][56][57][58] In the present study, human FSHD myoblasts were injected into immunodeficient Rag mice, a validated mouse model for the analysis of muscle regeneration in the context of xenogenic MT. The implantation results we obtained were close to that reported previously [47][48][49] and confirmed that myoblasts prepared from unaffected FSHD muscles, even used at the 6th and 7th passages, take part into in vivo muscle regeneration. The overall number of dystrophin-positive fibers was inferior to that reported previously in immunocompetent models of muscular dystrophies in the context of syngenic or allogenic MT.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the evaluation of transplantation outcome has been performed 1 month after transplantation, a time course that is of general use in human and animal MT assays. 9,16,17,20,31,47,49 This model was not regarded helpful to evaluate the longterm persistence of muscle fibers harboring the human mutated genes. Indeed, a negative selection of muscle fibers expressing the mutated gene could occur with time in the healthy environment of mouse muscle fibers, and this selection would not be representative of the situation presented in FSHD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations